Quasi-periodic signatures of Jupiter’s rotation in the tailside magnetosheath: Observations from Juno and Voyager-2 at ∼100–200 Jupiter radii - Zhonghua Yao; Ruilong Guo; Zhili Zeng; Binzheng Zhang; Jinyan Zhao; Tianran Sun; Wenya Li (Science China Earth Sciences, 2026)
Jupiter has the largest planetary magnetosphere in our solar system, and the rapid planetary rotation imposes a strong centrifugal force on the iogenic plasmas, forming a rotating magnetodisc. An inside-out compression of the magnetopause is expected on the dayside, while in the tail region, the interaction near magnetopause is poorly understood. By comparing particle and wave features near the magnetopause at different distances, we reveal quasi-planetary rotation periodic magnetic depressions in the magnetosheath near the magnetopause at dawnside (local time ∼6 h) at about 100 R J and post-midnight (local time ∼3 h) at about 200 R J . Accompanied by the magnetic depressions, energetic particle enhancements were observed, suggesting acceleration processes on the boundary. The strong magnetic perturbations and energetic particle enhancements are likely consequences of magnetospheric flow compression on the boundary. Particularly, the Voyager 2 observations made at about 200 R J in the tail provide key clues in understanding Jovian magnetotail dynamics and flow circulations.